Risk of CVD Following Radiotherapy for Head and Neck Cancer: An Updated Systematic Review and Meta-Analysis - Lin, Ping-Yi; Cheng, Ping-Chia; Hsu, Wan-Lun; Lo, Wu-Chia; Hsieh, Chen-Hsi; Shueng, Pei-Wei; Liao, Li-Jen (Frontiers in Oncology, 2022)
Background The relative risk for cerebrovascular disease (CVD) is increased in patients with head and neck cancer (HNC) treated with radiotherapy (RT). However, the current relative risk for CVD following RT has not been well clarified. The purpose of this study was to analyze the effect of RT and update the risk of CVD following RT in HNC patients through a systematic review and meta-analysis. Material and Methods We conducted an online database search and systematic review of observational studies that reported on CVD and extracranial carotid stenosis in patients with HNC who had undergone RT. Articles published in Medline and PubMed from 1980 to 2021 were identified and collected. Results Of the forty-seven articles identified from PubMed and forty-four articles identified from 3 systematic reviews, twenty-two studies were included. We found that neck RT was a significant risk factor for CVD (HR 3.97, 95% CI: 2.89-5.45). Patients with HNC treated by RT had an increased OR (7.36, 95% CI: 4.13-13.11) for CVD, and approximately 26% (95% CI: 22%-31%) of HNC patients treated with RT were at risk for CVD with more than 50% reduction in carotid diameter. Conclusion The risk of CVD is increased in patients with HNC treated by RT, and recent improvements in RT techniques may have contributed to the decreased risk of CVD. These results suggest that regular follow-up and appropriate screening for CVD should be required for patients with HNC.